Estudo das propriedades estruturais, ópticas e fotoluminescentes do Sistema α-(Ag2-3x-yTRxLiy)WO4 (TR = Pr, Sm, Eu, Tb, Dy e Tm) - Pinatti, Ivo Mateus (2018)
Luminescent materials of different colors emission are of great interest for development of new or more efficient optical devices. Although many materials have been reported using different approaches, green synthesis and nanosized phosphors of high color rendering is still very limited. Tungstate matrix can be considered as ideal host lattice for dopants as they possess high thermal, chemical and physical stability. In addition, silver compounds can be an excellent material for biomedical application due to its low toxicity and bacteriostatic properties, which in turn can be used in the health area. This thesis aims to investigate the structural, optical and photoluminescent properties of the system α-(Ag2-3x-yRExLiy)WO4 (RE = Pr, Sm, Eu, Tb, Dy e Tm) prepared by the coprecipitation methodology. This experimental procedure was fast, simple, and efficient to prepare these inorganic materials. The samples were investigated by X-ray diffraction with Rietveld refinement analysis, Raman and Ultraviolet-visible spectroscopy, and Photoluminescence measurements. The morphology was analyzed by Field-Emission Scanning Electron Microscopy and Transmission Electron Microscopy. X-ray Photoelectron Spectroscopy was performed to verify the superficial composition and details. The phase of the nanocrystals was confirmed and the structural and optical properties were dependent of the Rare Earth and Lithium ions. The nanomaterials presented excellent photoluminescent behavior due to the combined matrix and Rare Earth luminescence as well as temperature and co-doping dependence. The nanorod morphology reinforces the preferred alignment, dense packing and directional emission characteristics. Inspired by the above considerations, these new materials may present new applications and superior characteristics for luminescent compounds as well as for biological purpose.